The Influence of Regulations and Managers’ Environmental Attitudes on Firms’ Environmental Management - Díaz Paz, Claudia Patricia (Pontificia Universidad Católica del Perú, 2020)
This study contributes to the literature related to firms’ practices as responses to institutional pressures. Specifically, the research evaluates the influence of regulations on firms’ environmental management and incorporates managers’ environmental attitudes as a partial mediator. The population was Peruvian large and medium manufacturing firms. A two-step covariance-based structural equation model tested the propounded hypothesis. The results support the direct, positive, and moderate influence of regulations on firms’ environmental management. The influence of regulations on managers’ environmental attitudes is direct, positive, and low. Managers’ environmental attitudes are not related to firms’ environmental management, and there is no partial mediation of environmental attitudes, either.

El presente estudio contribuye a la literatura sobre las prácticas empresariales como respuesta a las presiones institucionales. Específicamente, esta investigación evalúa la influencia de las regulaciones en la gestión medioambiental de las empresas, e incorpora las actitudes medioambientales de los gerentes y ejecutivos como un mediador parcial. La población estuvo constituida por grandes y medianas empresas peruanas manufactureras. La metodología de ecuaciones estructurales de dos pasos basada en el análisis de las covarianzas fue utilizada para evaluar las hipótesis propuestas. Los resultados evidencian la influencia directa, positiva y moderada de las regulaciones en la gestión medioambiental de las empresas. La influencia de las regulaciones en las actitudes de los gerentes y ejecutivos es directa, positiva y pequeña. Las actitudes medioambientales de los gerentes y ejecutivos no están relacionadas con la gestión medioambiental de las empresas, y la mediación parcial de las actitudes medioambientales no fue sostenida.
Keywords: Gestión ambiental; Ejecutivos--Actitudes; https://purl.org/pe-repo/ocde/ford#5.02.04